Would they dope? Revisiting the Goldman dilemma - Connor, J.; Woolf, J.; Mazanov, J. (British Journal of Sports Medicine, 2013)
Background/aim: Discussions of doping often report Goldman's sensational results that half of the elite athletes asked would take a drug that guaranteed sporting success which would also result in their death in 5 years' time. There has never been any effort to assess the properties of the 'Goldman dilemma' or replicate the results in the post World Anti-Doping Agency context. This research evaluated the dilemma with contemporary elite athletes.